PELATIHAN INSTALASI KOMPUTER, CLONING SISTEM OPERASI, SERTA MEMBUAT FILE SHARING PADA JARINGAN KOMPUTER - Juanda Hakim Lubis; Zulfikar Sembiring (Universitas Muhammadiyah Sumatera Utara, 2017)
The development of technology today, especially computer technology has been very advanced. Including in Indonesia have many computer products that are marketed with various types, prices and specifications. To address it then we as consumers should be careful in choosing and buying the hardware components. So we are not deceived by the cheap price offered but also must be more thorough on the quality of goods offered. In general, the solution if the consumer experiencing performance problems in the software is to install the computer on the computer service. Installation costs generally range from RP 50,000 - RP 75,000. Imagine if the consumer in a year to install 5 times, the cost incurred around RP 250,000 - RP 375,000. Though the computer installation process is very easy to learn and just need accuracy in the process of data format. Hardware and operating system specifications are still not realized by the public is the most important part in the performance of a computer. Knowledge of hardware specifications is crucial to the performance of a hardware, as well as operating systems that do not have viruses or malware can also improve computer performance. Based on that, direct exposure and practice will be given maximally to provide the required information